Illness and culture in the postmodern age - Morris, David B. (University of California Press, 1998)
The author of this book argues that postmodern illness is created at the interconnection of biology and culture. Morris analyzes the distinctive experience of illness in our time, taking cultural studies into a new area called 'biocultural' studies.